Anniversary 36th of the Detachment of Medical Sciences Carlos Juan Finlay - José Antonio Pomares Alfonso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
The article constitutes a meaningful remembrance of a professor who had the satisfaction of having been involved in the foundation of the Carlos Juan Finlay Medical Detachment, so as its evocation realized by Our Commander in Chief Fidel Castro. This Detachment is a reality today and 36 years after the author shares his memories with the readers of Medisur.